Mechanistic Insight into Salt Tolerance of Acacia auriculiformis: The Importance of Ion Selectivity, Osmoprotection, Tissue Tolerance, and Na+ Exclusion - Rahman, Md. M.; Rahman, Md. A.; Miah, Md. G.; Saha, Satya R.; Karim, M. A.; Mostofa, Mohammad G. (Frontiers in Plant Science, 2017)
Salinity, one of the major environmental constraints, threatens soil health and consequently agricultural productivity worldwide. Acacia auriculiformis, being a halophyte, offers diverse benefits against soil salinity; however, the defense mechanisms underlying salt-tolerant capacity in A. auriculiformis are still elusive. In this study, we aimed to elucidate mechanisms regulating the adaptability of the multi-purpose perennial species A. auriculiformis to salt stress. The growth, ion homeostasis, osmoprotection, tissue tolerance and Na+ exclusion, and anatomical adjustments of A. auriculiformis grown in varied doses of seawater for 90 and 150 days were assessed. Results showed that diluted seawater caused notable reductions in the level of growth-related parameters, relative water content, stomatal conductance, photosynthetic pigments, proteins, and carbohydrates in dose- and time-dependent manners. However, the percent reduction of these parameters did not exceed 50% of those of control plants. Na+ contents in phyllodes and roots increased with increasing levels of salinity, whereas K+ contents and K+/Na+ ratio decreased significantly in comparison with control plants. A. auriculiformis retained more Na+ in the roots and maintained higher levels of K+, Ca2+ and Mg2+, and K+/Na+ ratio in phyllodes than roots through ion selective capacity. The contents of proline, total free amino acids, total sugars and reducing sugars significantly accumulated together with the levels of malondialdehyde and electrolyte leakage in the phyllodes, particularly at day 150th of salt treatment. Anatomical investigations revealed various anatomical changes in the tissues of phyllodes, stems and roots by salt stress, such as increase in the size of spongy parenchyma of phyllodes, endodermal thickness of stems and roots, and the diameter of root vascular bundle, relative to control counterparts. Furthermore, the estimated values for Na+ exclusion and tissue tolerance index suggested that A. auriculiformis efficiently adopted these two mechanisms to address higher salinity levels. Our results conclude that the adaptability of A. auriculiformis to salinity is closely associated with ion selectivity, increased accumulation of osmoprotectants, efficient Na+ retention in roots, anatomical adjustments, Na+ exclusion and tissue tolerance mechanisms.